Procedural complexity independent of P2Y12 reaction unit (PRU) values is associated with acute in situ thrombosis in Pipeline flow diversion of cerebral aneurysms. Issue 3 (21st April 2018) - Jiang, Bowen; Bender, Matthew T; Westbroek, Erick M; Campos, Jessica K; Lin, Li-Mei; Xu, Risheng; Tamargo, Rafael J; Huang, Judy; Colby, Geoffrey P; Coon, Alexander L
Abstract : Background: Acute in situ thrombosis is an ischaemic phenomenon during Pipeline embolisation device (PED) procedures with potentially high morbidity and mortality. There is controversy regarding the role of platelet function testing with P2Y12 assay as a predictor of intraprocedural thromboembolic events. There is limited knowledge on whether procedural complexity influences these events. Methods: Data were collected retrospectively on 742 consecutive PED cases at a single institution. Patients with intraprocedural acute thrombosis were compared with patients without these events. Results: A cohort of 37 PED cases with acute in situ thrombosis (mean age 53.8 years, mean aneurysm size 8.4 mm) was matched with a cohort of 705 PED cases without intraprocedural thromboembolic events (mean age 56.4 years, mean aneurysm size 6.9 mm). All patients with in situ thrombosis received intra-arterial and/or intravenous abciximab. The two groups were evenly matched in patient demographics, previous treatment/subarachnoid hemorrhage (SAH) and aneurysm location. There was no statistical difference in postprocedural P2Y12 reaction unit (PRU) values between the two groups, with a mean of 156 in the in situ thrombosis group vs 148 in the control group (p=0.5894). Presence of cervical carotid tortuosity, high cavernous internal carotid artery grade, need for multiple PED and vasospasm were not significantly different between the two groups. The in situ thrombosis group had statistically significant longer fluoroscopy time (60.4 vs 38.4 min, p<0.0001), higher radiation exposure (3476 vs 2160 mGy, p<0.0001), higher rates of adjunctive coiling (24.3% vs 8.37%, p=0.0010) and higher utilisation of balloon angioplasty (37.8% vs 12.2%, p<0.0001). Clinically, the in situ thrombosis cohort had higher incidence of major and minor stroke, intracerebral haemorrhage and length of stay. Conclusions: Predictors of procedural complexity (higher radiation exposure, longer fluoroscopy time, adjunctive coiling and need for balloon angioplasty) are associated with acute thrombotic events during PED placement, independent of PRU values.